Freedom to build, not destroy attacks on Christians and their institutions - Esteves Sarto (Delhi Media House, 2002)
This author takes the reader through irrefutable facts & figures to prove that members of the Christian community have never lagged behind in patriotic fervour. He also leaves no one in doubt about the commitment of Christians to tread the path shown by
Keywords: Christians; Relation with state; Religious groups